Photoregulation of Cellular Morphology during Complementary Chromatic Adaptation Requires Sensor-Kinase-Class Protein RcaE in Fremyella diplosiphon - Bordowitz, Juliana R. (American Society for Microbiology (ASM), 2008)
We used wild-type UTEX481; SF33, a shortened-filament mutant strain that shows normal complementary chromatic adaptation pigmentation responses; and FdBk14, an RcaE-deficient strain that lacks light-dependent pigmentation responses, to investigate the molecular basis of the photoregulation of cellular morphology in the cyanobacterium Fremyella diplosiphon. Detailed microscopic and biochemical analyses indicate that RcaE is required for the photoregulation of cell and filament morphologies of F. diplosiphon in response to red and green light.